Cortical alpha activity predicts the confidence in an impending action - Kubanek, Jan; Hill, Jeremy; Snyder, Lawrence H.; Schalk, Gerwin (Frontiers in Neuroscience, 2015)
When we make a decision, we experience a degree of confidence that our choice may lead to a desirable outcome. Recent studies in animals have probed the subjective aspects of the choice confidence using confidence-reporting tasks. These studies showed that estimates of the choice confidence substantially modulate neural activity in multiple regions of the brain. Building on these findings, we investigated the neural representation of the confidence in a choice in humans who explicitly reported the confidence in their choice. Subjects performed a perceptual decision task in which they decided between choosing a button press or a saccade while we recorded EEG activity. Following each choice, subjects indicated whether they were sure or unsure about the choice. We found that alpha activity strongly encodes a subject’s confidence level in a forthcoming button press choice. The neural effect of the subjects’ confidence was independent of the reaction time, of eye movement, and of activity of forearm muscles. Furthermore, the effect was not explained by the sensory input modeled by a decision variable. Neither could the effect be explained by a general cognitive state, such as arousal or reward expectation, because the effect was specifically observed during button press choices and not during saccade choices. The neural effect of the confidence in the ensuing button press choice was strong enough that we could predict, from independent single trial neural signals, whether a subject was going to be sure or unsure of its button press choice. In sum, alpha activity in human cortex provides a window into the degree of a forming commitment to make a hand movement.